Insight into structure and assembly of the nuclear pore complex by utilizing the genome of a eukaryotic thermophile - Amlacher, Stefan; Sarges, Jan Phillip; Flemming, Dirk; Kunze, Ruth; Bork, Peer; Hurt, Ed (Cell, 2011)
Summary: Despite decades of research, the structure and assembly of the nuclear pore complex (NPC), which is composed of ∼30 nucleoporins (Nups), remain elusive. Here, we report the genome of the thermophilic fungus Chaetomium thermophilum (ct) and identify the complete repertoire of Nups therein. The thermophilic proteins show improved properties for structural and biochemical studies compared to their mesophilic counterparts, and purified ctNups enabled the reconstitution of the inner pore ring module that spans the width of the NPC from the anchoring membrane to the central transport channel. This module is composed of two large Nups, Nup192 and Nup170, which are flexibly bridged by short linear motifs made up of linker Nups, Nic96 and Nup53. This assembly illustrates how Nup interactions can generate structural plasticity within the NPC scaffold. Our findings therefore demonstrate the utility of the genome of a thermophilic eukaryote for studying complex molecular machines.